Histology of psoriatic erythroderma in infants: Analytical study of eight cases - Parimalam Kumar; Jayakar Thomas; Devaraj Dineshkumar (Wolters Kluwer Medknow Publications, 2015)
Background: Erythroderma in infants is a rare condition of varied etiology. Psoriasis is now emerging as the most common cause of erythroderma in infants. Early diagnosis of the etiological cause much depends upon the histological confirmation, which is essential for an early and appropriate treatment. Aim: It was aimed to study the histological findings in psoriatic erythroderma in infants. Materials and Methods: A total of 8 infants up to 1 year of age presenting with erythroderma, clinically suspected to be of psoriatic etiology attending private clinic were included. After detailed history taking and astute clinical exam, all of them were biopsied. In case 6, with a positive family history of psoriasis and asthma in parents, biopsy was taken from two sites. The histological findings of all nine biopsies were studied and analyzed. Results: Histology of all eight children showed psoriasi form pattern with acanthosis (AC) and dilated papillary capillaries (PC). Spongiform (SF) pattern was seen in the second biopsy (6b) of child with features of both psoriasis and atopy. SF pustule of Kogoj or Munro's abscess was not seen in any of them. Conclusion: Regular AC and PC dilatation were the consistent histological findings observed in infants with erythrodermic psoriasis. These were the early findings observed in younger infants. Co-existence of psoriasis with atopic dermatitis may indicate a common pathogenic mechanism or an immunogenetic spin-off.